An antibody- and synthetic peptide-defined rubella virus E1 glycoprotein neutralization domain. - Wolinsky, J S (1993)
We previously described a monoclonal antibody (MAb) library generated by infecting BALB/c mice with rubella virus (RV) and selected by an enzyme-linked immunosorbent assay (ELISA) using purified virion targets. Plasmid pARV02-01, which expresses the fusion protein RecA1-35-GIGDLGSP-E1(202)-E1(283)-GDP-LacZ9-1015 in Escherichia coli, was shown to be a ligand for MAbs E1-18 and E1-20 (J. S. Wolinsky, M. McCarthy, O. Allen-Cannady, W. T. Moore, R. Jin, S. N. Cao, A. Lovett, and D. Simmons, J. Virol. 65:3986-3994, 1991). Both of these MAbs neutralize RV infectivity. A series of five overlapping synthetic peptides was made to further explore the requirements of this MAb binding domain. One of these peptides (SP15; E1(208) to E1(239)) proved an effective ligand for both MAbs in the ELISA. Stepwise synthesis of SP15 defined the minimal amino-terminal requirement for binding MAb E1-18 as E1(221) and that of MAb E1-20 as E1(223); the minimal carboxyl-terminal requirement is uncertain but does not exceed E1(239). Immunization of mice and rabbits with SP15 induced polyvalent antibody reactive with SP15, with other overlapped and related but not unrelated synthetic peptides, and with RV. The rabbit anti-SP15 antibody showed neutralization activity to RV similar to that of MAbs E1-18 and E1-20 but lacked hemagglutination inhibition activity. These data define a neutralization domain on E1 and suggest that the RV epitopes conserved by SP15 may be critical for protective host humoral immune responses.